The prevalence of human T‐lymphotropic virus type 1 & 2 (HTLV‐1/2) in South African blood donors. Issue 5 (4th April 2019) - Vermeulen, Marion; Sykes, Wendy; Coleman, Charl; Custer, Brian; Jacobs, Genevieve; Jaza, Jabulisile; Kaidarova, Zhanna; Hlela, Carol; Gessain, Antoine; Cassar, Olivier; Poole, Colwyn; Ingram, Charlotte; et al.
Abstract : Background and objectives: Donated blood is not currently screened for human T‐cell lymphotropic virus (HTLV) in South Africa. Several small studies have detected HTLV‐1 in South Africa, but prevalence by geographic region or population group is unavailable. Materials and Methods: We performed a large seroprevalence study of South African blood donors during 3 months in 2013. All geographic regions except the Western Cape were included, and Black and Coloured (local term for mixed race) donors were oversampled. Identity‐unlinked plasma samples were screened with the Abbott Prism HTLV‐1/2 assay, and repeatedly reactive samples were tested by the Inno‐LIA HTLV‐1/2 Score confirmatory assay. Odds ratios were calculated with multivariable logistic regression. Results: Of 46 752 donors tested, 133 (0·28%) were initially reactive, 111 (0·24%) repeatedly reactive and 57 (0·12%) confirmed positive for HTLV‐1; none were HTLV‐2 positive. Prevalence was 0·062% weighted to annual blood donations but highly concentrated in the Black population group (OR = 20·24 CI: 2·77–147·88); higher in females than males (OR = 1·81 CI: 1·06–3·08); and in donors aged >50 years compared to ages 16–19 (OR = 6·4 CI: 2·95‐13·86). After controlling for age, sex and population group, there was no difference in prevalence between new and repeat blood donors or among geographic regions within South Africa. Conclusions: We conclude that HTLV‐1 infection is widespread among the Black population of South Africa and its epidemiology is similar to other endemic areas. Because South Africa is increasing its recruitment of Black blood donors, the implications for blood screening require further consideration.